Mathematics
Rigby
11

99 points and brainliest to whoever answers

+1
(2) Answers
Leonidaz

x² + 6x – 7 = 0 Quadratic Formula . . . __________ -6 ±√ 6² - 4(1)(-7) ------------------------- = x . . . . 2(1) . . . ________ -6 ±√ 36 + 28 --------------------- = x . . . . 2 . . . ____ -6 ±√ 64 -------------- = x . . 2 -6 ± 8 -------------- = x . . 2 x = -7 or x = 1 <==ANSWERS Completing the Square below x² + 6x – 7 = 0 x² + 6x = 7 x² + 6x + 9 = 7 + 9 x² + 6x + 9 = 16 (x + 3)² = 16 . ______ . . . ___ √(x + 3)² = ±√16 x + 3 = ± 4 x = -3 ± 4 x = -7 or x = 1 <== anwser

hannah337

the answer is y=(x-3)^2-2

Add answer